TECMED (CIPEEX, 2024)
TO IMPROVE THE QUALITY AND USER EXPERIENCES IN APPLICATIONS AND VIRTUAL ENVIRONMENTS, THE INTERFACE WORKS WITH THE INTERPOSITION OF TOOLS THAT HAVE THIS FUNCTION, AIMING TO FACILITATE AS MUCH AS POSSIBLE THE REALIZATION OF THE APPOINTMENT SCHEDULING IN A VIRTUAL WAY, WHICH IS THE PURPOSE OF OUR SOFTWARE. IN THIS WAY, IN ORDER TO PROVIDE THE PERSONA WITH THE MOST PRACTICAL, ACCESSIBLE AND WELCOMING EXPERIENCE WHEN ACCESSING OUR APPLICATION. IN THE FOLLOWING WORK, A DEMONSTRATION OF HOW A HEALTH APP WOULD WORK FOR THE MOSTLY MIDDLE-AGED CUSTOMER WAS PROMOTED. IN A RANGE OF AREA GIVEN BY THE USER'S LOCATION, THE TECMED APPLICATION WOULD SHOW THE NEAREST HOSPITALS AND HEALTH CENTERS WITH THE EASIEST ACCESS TO THE CUSTOMER. ITS SYSTEM ALSO INCLUDES DOCTORS REGISTERED IN HOSPITALS AND THEIR RESPECTIVE LATTES, IN ADDITION TO THE USER'S PREFERENCE FOR THE HEALTH PROFESSIONALS INCLUDED IN THE APP. IT IS ALSO AVAILABLE WHICH FORMS OF PAYMENT ARE ACCEPTED BY SERVICE INSTITUTIONS TO PROVIDE MAXIMUM INFORMATION AND GREATER EFFICIENCY TO USERS IN SCHEDULING APPOINTMENTS. POSSIBLY, AND INITIALLY, AIMED AT THE PRIVATE BUSINESS, BUT IF THAT'S THE CASE, IT COULD EASILY BE IN THE PUBLIC SECTOR AS WELL. THE METHODOLOGY USED WAS THE DEFINITION OF THE PERSONA, THE FUNCTIONAL AND NONFUNCTIONAL REQUIREMENTS, AS WELL AS THE USE OF USABILITY LAWS, IN ADDITION TO THE DESIGNATION OF THE COLOR PALETTE, BASED ON THE CONCEPTS OF COLOR PSYCHOLOGY. FINALLY, WE CARRY OUT THE USER JOURNEY TO THEN PRODUCE THE PROJECT PROTOTYPE. THE RESULTS WE SEEK TO ACHIEVE WOULD BE AN IMPROVEMENT IN THE CONDITION OF CUSTOMER SERVICE IN THE HEALTH AREA, IN ADDITION TO INCREASING ACCESSIBILITY THROUGH HELP FUNCTIONS FOR CUSTOMERS WHO HAVE SOME COMORBIDITY. ALSO, MONITORING AND GUIDANCE OF CONSULTATION PLANS WOULD BE MADE AVAILABLE, WHICH WOULD FACILITATE THE EXPERIENCE AND BRING A BETTER QUALITY OF LIFE TO USERS.
Keywords: TECMED; Health; Acessibility